The Effect of Leadership and Implementation of Licensing Policy on Service Satisfaction for Building Licenses in Bandung City, West Java Province (Study at the Investment Office and One Door Integrated Service) - Anwar Rosshad (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
The satisfaction of the service of the Building Permit (BP) which is the government's obligation in realizing the order to maintain the order of people's lives in a calm, peaceful and peaceful manner is an indicator of good governance. In addition, BP service is a mandatory government affair according to Law No. 23 of 2014. The purpose of this research is to analyze and determine the influence of leadership and licensing policy implementation on BP service satisfaction in Bandung City, and to find a new concepts/models of service satisfaction. The research method used is quantitative with a total sample of 248 respondents from a total population of 682 people. In data analysis, Structure Equation Model is used by processing the data collected through questionnaire data. The results of this study, which were obtained from path analysis and t-value, the effect of causality between Leadership was 0.32 (5.01) and Licensing Policy Implementation was 0.72 (9.47) on BP Service Satisfaction, all of the results were "positive and significant". The findings of this research are the Model of Emotional Service Satisfaction (MESS) which is determined by three factors, namely change-oriented leadership behavior, bureaucratic structure, and human resources. The conclusion of the research is that BP service satisfaction is in good category, all three hypotheses are accepted, and the causality relationship is positive and significant. So that new models and concepts are obtained in the field of public service satisfaction.